Typology and Effectiveness of Al-Quran Memorization Applications - Akbari, M. Yudo Agresi; Kusaeri; Bakar, M. Yunus Abu; Rusydiyah, Evi Fatimatur (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This research aims to determine the typology of Al-Quran memorization application models and their effectiveness in learning Al-Quran tahfidz. The research method used in this research is Systematic Literature Review (SLR). SLR is a method used to comprehensively investigate relevant literature to understand the status of existing research on a particular topic. The data sources used come from Scopus and Semantic Scholar from 2019-2024 using the Publish and Perish (PoP) application. The results of this research found that there are 3 tahfidzul Quran application models: Voice Technology-Based Model, Gamification-Based Model and Modular-Based Model. Regarding effectiveness, it was found that the Voice Technology Based Model was still less effective. Meanwhile, the Gamification-Based Model has been proven to be effective in supporting learning. As for the Modular Based Model, there are those that have been proven to be effective in supporting memorizing learning of the Koran and there are also those that have not been proven because they are still in the needs exploration study stage. Further studies are needed regarding the challenges and obstacles as well as strategies for their use so that the development of the Tahfidz Al-Quran application model can be more effective in supporting the Al-Quran learning process.